The Impact of a RecoveryTraining CourseAccompanied by an Innovative Device on some Physiological Changes, Body Changes and Achievement of Jerking by Weightlifter - Obaid, Mohammed Hussein; Oudah, Maysoon Alwan (International Journal of Psychosocial Rehabilitation, 2019)
The recovery process is considered a physiological condition represented in the return of the body’s systems to their normal rates or as close to that as possible, and from this we can know that the correct exchange between efforts and recovery processes is among the basic factors necessary for players to reach the highest levels, through Training course,technological development and modern methods are related to different training ways and systems. As such,this study aims to know the impact of a recovery training course on some hormones, body changes and jerking achievement of weightlifters. The researchers used the experimental approach for it suitability to achieve the aims. The two testers, who were 10weightlifters, were divided into two experimental and control groups, each of them consisted of (5weightlifters). With the help of an engineering cadre and determine the study variables for some Physiological changes as (T4 - T3 - Cortisol – Testosterone cpk Enzyme - Heart pulse rate) and Body Change for (maximum strength -endurance strength- Flexibility- achievement)) for weightlifting beginners. After the pre-tests, and after that the recovery course was applied for a period of (12) weeks every week, three recovery units, and after completion, the post-tests were conducted, and the data were collected and statistically processed through the use of the statistical package (spss). The course improves some Physiological changes, strength and achievement for weightlifters.